Gambaran Asma Bronkhial Pada Anak Di Beberapa Wilayah Indonesia - Syafri, Muh Agung Syafwan; Sartika, Suriana Dwi; Wahyuddin, Bob (Fakultas Kedokteran Universitas Bosowa, 2025)
Asma is a chronic respiratory condition that is usually found in both children and adults. The frequency of asthma in children varies greatly across countries in the world, ranging from 1-18 percent. Narrowing and obstruction of the respiratory system occurs due to bronchial wall thickening, smooth muscle contraction, mucosal edema, mucus hypersecretion. This study aims to determine the description of asthma in children in several regions in Indonesia based on age, gender, exposure to cigarette smoke and pets. The method in this research is a descriptive study by means of a regular study of twenty-three jurnal related to the description of asthma in children in several regions in Indonesia objective criteria consisting of age, gender, exposure to cigarette smoke, and pets. Based on the results of a study of twenty-three journals that specifically examine the picture of bronchial asthma in children in several regions in Indonesia, it can be concluded that the distribution of age, gender, exposure to cigarette smoke, and pets has a relationship with the picture of bronchial asthma in children in several regions in Indonesia.